Candy for Cows: Improving Nutritional Status of Cows in The Sarono Makmur Yogyakarta Farmer Group - Akhiroh, Ninuk Sholikhah; Kismini, Elly; Arsi, Antari Ayuning; Hidayah, Nur (Universitas Negeri Semarang, 2024)
Cattle farming on the slopes of Mount Merapi is a livelihood sector that has existed for a long time, and is a tradition inherited from generation to generation. Cattle farming on the slopes of Mount Merapi or more precisely in Cangkringan District, Sleman Regency not only requires green food, but also concentrates and supplements. The provision of concentrates and supplement has been carried out by bombardment. Therefore, it is necessary to introduce another way to provide nutritions for cows, which has several advantages compared to feeding, namely giving concentrate candy. concentrate candy has several advantages, such as, it can be made using ingredients found around the farmer, and portions of the candy can be used to provide nutrition for a certain period of time, for example one month, so the farmer does not have to bother with bombardment everyday. This is the basis for carrying out community service in the form of training in making concentrate candy for cows. This community service program is implemented through a series of activities which includes socialization, Focus Group Discussion (FGD), and training/simulation. The socialization was carried out with explanations by an animal nutrition expert about the ingredients and contents of the candy, and continued with discussion and practice in making candy with facilitation and supervision from the community service team and cow feed expert. With this program, it is hoped that the community will be developed, empowered, and independent, so that they can implement this program in a sustainable manner.